A fluorescence sensing method for brilliant blue with gold nanoclusters based on the inner filter effect. Issue 37 (1st September 2020) - Liu, Haijian; Wang, Miao; Li, Zhenxiang; Xin, Chengjie; Huang, Guofu
Abstract : Due to the inner filter effect (IFE) between Brilliant Blue (BB) and gold nanoclusters (AuNCs), a simple and rapid approach for BB detection was developed. Abstract : Due to the inner filter effect (IFE) between Brilliant Blue (BB) and gold nanoclusters (AuNCs), a simple and rapid approach for BB detection was developed. Since the absorption spectrum of BB has a good overlap with the emission spectrum of the AuNCs, the fluorescence of the AuNC solution was quenched after adding BB. Under optimal conditions, a good linear relationship for detection of BB was obtained from 0.05 to 7.5 μM, and the detection limit was 0.0167 μM. More importantly, the assay was successfully applied to assess BB in food samples such as hard candy, chocolate and dried blueberries, showing its potential in food quality control in the future.